Cybele, Attis, and related cults : essays in memory of M.J. Vermaseren - Vermaseren, M. J.; Lane, Eugene, 1936- (Religions in the Graeco-Roman World, 1996)
This volume brings together articles on the cult of the mother-goddess Cybele and her consort Attis, from the emergence of the religion in Anatolia through its expansion into Greece and Italy to the latest times of the Roman Empire and its farthest extent west, the Iberian Peninsula. It combines the work of established scholars with that of young researchers in the field, and represents a truly international perspective. The reader will find treatment inter alia of Cybele's emasculated priests, the Galli; the dissemination of Cybele-cult through the harbour city, Miletus; the cult of Cybele in Ephesus; the rock-cut sanctuary of Cybele at Akrai in Sicily; the competition between the Cybele-cult and Christianity; and the role of Attis in Neo-Platonic philosophy.